In the Skin of a Lion: A Novel - Ondaatje, Michael (Penguin Random House Canada, 1996)
n the Skin of a Lion is a love story and an irresistible mystery set in the turbulent, muscular new world of Toronto in the 20s and 30s. Michael Ondaatje entwines adventure, romance and history, real and invented, enmeshing us in the lives of the immigrants who built the city and those who dreamed it into being: the politically powerful, the anarchists, bridge builders and tunnellers, a vanished millionaire and his mistress, a rescued nun and a thief who leads a charmed life. This is a haunting tale of passion, privilege and biting physical labour, of men and women moved by compassion and driven by the power of dreams—sometimes even to murder. --Publisher's description
Keywords: Fiction; Love stories; Ontario Toronto; Poor; Social Class and Equality; Toronto (Ont.)